2013
DOI: 10.2147/opth.s31016
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles for antiangiogenesis factors in management of ocular disease

Abstract: The first antivascular endothelial growth factor (anti-VEGF) was developed as an anticancer drug for colonic carcinomas. Since then, anti-VEGFs have developed in scope and indications. They have revolutionized the treatment of exudative macular degeneration and have had a major impact on treatment of several other conditions. This has resulted in an increased number of patients seeking treatment with new treatment options and has had a considerable financial impact on health care resources. Anti-VEGFs have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…; Saeed et al. ). A series of clinical trials have supported the efficacy of anti‐VEGF agents for treating AMD (Rosenfeld et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Saeed et al. ). A series of clinical trials have supported the efficacy of anti‐VEGF agents for treating AMD (Rosenfeld et al.…”
Section: Introductionmentioning
confidence: 98%
“…Several clinical trials have shown that intravitreal injections prevent vision loss in the majority of patients and in some cases, significantly improved vision 16 20–22 with low numbers of serious adverse effects. 8 Subsequently, anti-VEGF therapy has become the standard clinical option to treat patients with AMD.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Subsequently, anti-VEGF therapy has become the standard clinical option to treat patients with AMD. 18 20 21 In 2011, anti-VEGF therapy was also introduced as treatment for diabetic macular oedema and central retinal vein occlusion. 1 18 23 …”
Section: Introductionmentioning
confidence: 99%
“…Should venous outflow improve naturally or through prompt treatment, collateralisation may become unnecessary. While many clinicians consider collateralisation to be beneficial, it may not serve to expedite the resolution of macular oedema despite reducing interstitial hydrostatic pressure within the retina . In fact, final VA may be worse in the presence of collaterals, perhaps testament to the severity of the initial occlusion.…”
Section: Clinical Featuresmentioning
confidence: 99%